PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IX SMP MUHAMMADIYAH RAMBAH - Utami, Sri; -, Arcat; -, Hardianto (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
One of ways to solve this problems are Applying of cooperative learning model send greetings and questions technique toward. This research to know the result of student learning using cooperative learning model send greetings and questions technique toward to the ninth grade student of SMP Muhammadiyah Rambah. The data were analyzed using t-test at significance level Î±=0.05 and df=